Literature Review: Fluid Therapy in Preventing Hypotension in Section Caesarean with Spinal Anesthesia - Wilis Sukmaningtyas; Tin Utami (STIKes Patria Husada Blitar, 2022)
Background: Hypotension is a complication that often occurs in section Caesarea with spinal anesthesia. Severe hypotension poses serious risks to the mother (such as loss of consciousness) and the baby (such as oxygen deprivation and brain damage). So to prevent hypotension, it can be done by giving crystalloid or colloid fluid therapy after spinal anesthesia is carried out. Methods: Articles were searched using 3 databases (PubMed, Pro-Quest, and Google scholar) with a randomized controlled trial research method. The literature is limited between 2010 and 2019. Results: Seven articles with average results on administration of both preloaded and concomitant crystalline and colloidal fluids can reduce the incidence of hypotension, but for this technique Hypotension cannot be completely reduced and should be used with Vasopresor. Discussion and conclusion: The incidence of hypotension after spinal anesthesia should be treated immediately to prevent injury to the kidneys, heart, and brain by giving oxygen and increasing the rate of infusion (colored) of 100 ml of colloid or crystalloid fluid within the first 5 minutes or less for improving blood pressure. If blood pressure is still low after fluids are given, a vasoconstrictor such as ephedrine 5-10 mg can be gradually given.